Work Commitment to Contract Employees In Government Organization - Anggraini, Shintabella Artha; Hapsari, Maharani Tyas Budi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This research discusses the work commitment of contract servant employees in government agencies. Work commitment rears to the voluntary action’s employees take to remain with an organization. Contract servant employees do not receive the same benefits and welfare as civil servant employees. Therefore, employees require work commitment that can have positive impacts on their work, such as improved performance, lower turnover intention, and increased job quality for contract servant employees. The aim of this study is to determine the reasons or factors that drive contract servant employees to stay in an organization for a significant period despite having a considerable workload. The research subject consists of three contract servant employees and two significant others in a government institution. The research data consist of voice recordings that were analysed using Atlas.ti. The data analysis was categorized according to aspects or coding. The researcher described analysed the data in detail to draw conclusions. The research findings indicate that the main reason contract servant employees are committed to the organization are their realistic expectations, such as being appointed as PPPK employees under ongoing government program, and their hope of receiving better welfare attention from the institution. These three subjects hope that their expectations will be fulfilled as they have been working and committed to the organization for a significant period of timer.Dalam penelitian ini membahas tentang komitmen kerja yang dimiliki oleh pegawai non-ASN pada instansi kepemerintahan. Komitmen kerja merupakan tindakan sukarela yang diberikan pegawai kepada suatu instansi dengan tujuan untuk tetap berada di instansi. pegawai non-ASN tidak mendapatkan benefit maupun kesejahteraan yang sama dengan pegawai ASN, hal ini tentu saja mempengauhi kinerja pewai non-ASN. Dengan hal itu, pegawai membutuhkan komitmen kerja yang dapat memebrikan dampak baik dalam pekerjaannya seperti kinerja yang meningkat, rendahnya keinginan turnover, dan meningkatnya kualitas kerja pegawai non-ASN. Tujuan penelitian ini untuk mengetahui alasan atau hal yag mendasari pegawai non ASN untuk tetap bertahan di instansi dengan periode jabatan yang cukup lama dan jobdesk yang cukup banyak. Subjek penelitian ini adalah pegawai non ASN sejumlah tiga orang dan dua significant other pada suatu instansi pemerintah dengan data penelitian berupa voice record yang dilakukan analisa menggunakan Atlas.ti. Analisa data dibagi dalam kategori-kategori sesuai aspek atau sering disebut juga coding. Peneliti menjabarkan dan menganalisa dengan rinci sehingga memperoleh kesimpulan dari data yang telah diambil. Hasil penelitian manyatakan alasan utama pegawai non-ASN berkomitmen pada instansi, pegawai non ASN memiliki harapan-harapan realistis yang, yaitu diangkatnya menjadi pegawai PPPK seperti program pemerintah yang sedang berjalan, dan diperhatikan lagi kesejahteraannya oleh instansi. ketiga subjek berharap harapannya ini dapat terwujud karena sudah bekerja dan berkomitmen cukup lama dengan instansi.